Detection of Oral Entamoeba Gingivalis in a Kut Population with Gingivitis and Periodontal disease (Eurasian Journal of Research, Development and Innovation, 2024)
With regard to the parasitological confirmation, E. gingivalis trophozoites were evident microscopically within all 22 positive specimens.The study involved 30 persons: 15 women and 15 men. In the studied group. The study consisted of the observation of samples derived by way of buccal swabs under a microscope in a search for Entamoeba gingivalis trophozoites. Such protozoa were found in 22 patients, but no in 7 patients . Among the samples derived from women, the protozoa were in 13 (59.09%), and among men, in 9 subjects (40.91%).It was found during the examination that the percentage of non-smoking individuals was the highest, 95.54%, and the lowest percentage of smoking individuals was 4.55%. The number. The total number of people examined was N = 30.Out of 30 investigated studies, 30 specified a mean age for their sample size. Results showed an increase in prevalence on (21-30) the age of the patients, the lowest prevalence was reported lass 10 age and (51-60) age